Perancangan Sistem Informasi dan Tempat Penyimpanan Master Warna untuk PT UBS - Erik Tanzil; Iwan Halim Sahputra (Jurnal Titra, 2020)
PT UBS is a company that produces gold jewelry. Finishing process at PT UBS involves plating and final QC process that needs color masters. Color masters are finished goods that are stored as color standards. The color masters have an expiration date. The company has 4 problems: color masters are not easy to be located to be used during the final QC process, many color masters are out of date, the overstock of some color master candidates, and sometimes they found no colos master candidates. The objectives of this study are to design information system for the color master expiration dates, to design information system for the color master candidates, and to design a new storage for the color masters. Microsoft Excel with Visual Basic for Applications (VBA) is used to design the information systems. SketchUp and anthropometry data are used to design the new storage. The results of this study are 2 information systems and 1 storage design. The information systems will facilitate expiration dates control and inventory control. The storage design will increase efficiency of final QC process since color masters are located easily.